Production of Polyhydroxybutyrate (Bioplastic) and its Biodegradation by Pseudomonas Lemoignei and Aspergillus Niger - S. Kumaravel; R. Hema; R. Lakshmi (E-Journal of Chemistry)
The biodegradation of polyhydroxybutyrate (PHB) and its copolymer polyhydroxy butyrate-co-hydroxyvalerate (PHB-co-HV) was studied. Bacterial as well as fungal isolates were isolated from the local industrial ecosystem. All these isolates were tested for the degradation of the above polymers in assay agar medium as well in liquid cultures. The culture biomass and the clear zone around the colonies were measured to evaluate the activity of these isolates. In all, the fungal isolates were found to degrade these polymers more rapidly when compared to bacteria, due to their versatile depolymerase activities.